Implikasi Perselisihan Amerika Serikat dengan Rusia terhadap Konflik Suriah - Andriani Dyah Arum; Reni Windiani (Journal of International Relations Diponegoro, 2018)
The Syrian conflict is an armed conflict between the Syrian Government and its oppositionthat emerged in March 2011. This conflict has caused enormous numbers of casualties andis still unresolved. This research aims to describe a brief history of Syrian Conflict, thecomplexity of US and Russia involvements in the conflict that tends to have confrontationpattern of offensive realism, and the implications of the confrontation. This research usesqualitative methods and uses secondary and primary data sources. The results of thisresearch shows that the implications of confrontation between two superpowers (US andRussia) to Syrian Conflict resettlement process are; limiting the performance of the ISSGas a facilitator of negotiations, making the search for solutions and conflict resolutionprocess by UN in Syria deadlocked which leads to the emergence of injustice againstperpetrators of war crimes.